Chinese literary works translated into Baba Malay: a bibliometric study - Yoong, S.K.; Zainab, Awang Ngah (Department of Library & Information Science, Faculty of Arts and Social Sciences, Universiti Malaya, 2002)
Analyses 68 unique titles of Baba translated works published between 1889 and 1950. The titles are held in the libraries of the University of Malaya (UM), Science University Malaysia (USM), National University of Malaysia (UKM), the Dewan Bahasa dan Pustaka (DBP), National University of Singapore (NUS), National Library of Singapore (NLS) and the British Library (BL). The results reveal three periods of active publication of Baba translated works. A total of 18 works were translated before World War I, followed by 10 just after the war, 39 titles were published before the break of the World War II and 1 was identified in 1950. There were 103 persons involved in the 68 translated works, some of whom are responsible for more than one title. The most prominent translators were Chan Kim Boon, Wan Boon Seng, Seow Chin San and Lee Seng Poh. Some of the translators were also be editors, illustrators or editors. There were 31 publishers and 21 printing presses involved, all were located in Singapore. The most active publishers were Wan Boon Seng, Kim Seck Chy Press and Nanyang Romanised Malay Book Co. The translated works mainly cover historical classical Chinese stories, chivalrous stories, romances, folklore and legends. The titles were priced between 10 cents to 2 dollars in Straits currency. The University of Malaya Library held the largest number of unique title (62) out of which 15 were unique titles.